Comércio eletrônico modificações econômicas e funcionais na esfera da circulação - Di Giorgi, Fernando (2016)
The focus of this dissertation is e-commerce, a sales channel that emerged from innovations in information and communications technology (ICT). Using a Marxist framework, the aim of this work is to explain the changes occurring in the movement of goods in retail derived from e-commerce, and its contradictions. As a secondary objective, the dissertation also aims to explain (a) the new driving forces of capital concentration and changes in the retail market structure, (b) changes and innovations in the services market in general, induced by electronic commerce, (c) functional impairment of trade and the direct selling by industry, (d) the extent of technological platforms used by the biggest online stores to provide selling services for small retailers (the marketplace function) and (e) the new opportunities derived from multi/omni channel commerce technology